Integration of Electric Vehicles (EVs) with Electrical Grid and Impact on Smart Charging - Ahsan, Md Shameem; Tanvir, Faysal Amin; Rahman, Md Khaledur; Ahmed, Manam; Islam, Md Saiful (Information Technology and Science (ITScience), 2023)
Integrating Electric Vehicles (EVs) with the electrical grid is a pivotal aspect of modern transportation systems. This integration poses multifaceted challenges and opportunities, influencing the grid's stability, energy management, and environmental sustainability. Smart charging solutions emerge as a crucial mechanism to address these challenges by optimizing charging patterns, balancing grid demand, and maximizing renewable energy utilization. This abstract delves into the impacts of EV-grid integration, exploring the interplay between smart charging solutions and grid dynamics while considering the implications for energy infrastructure, user behavior, and environmental impact. It also provides a concise overview of EV grid integration's key issues. It highlights the crucial role of smart charging technologies in addressing them and paving the way for a sustainable future of transportation and energy.